STUDY OF DIRECTING MESOPOROUS COMPOUNDS ABILITY DURING INTERZEOLITE TRANSFORMATION FAU TO CHA - Setiawan, Tomi
CHA zeolite with small micropores (3.8 x 3.8 Å) is composed of composite building units (CBU) in the form of d6r and cha. CHA zeolite with a high Si/Al ratio (Si/Al > 5) or known as SSZ-13 zeolite is very selective in various reactions such as synthesis of olefins from methanol (MTO), synthesis of propylene from ethylene (ETP), reduction of NOx, and CO2 gas separation. CHA zeolite commonly synthesized using FAU zeolite as the parent zeolite in the interzeolite transformation method due to similarity of CBU in the form of d6r, interzeolite transformation FAU to CHA could using a organic structure directing agent (OSDA) in the form of TMAdaOH or without OSDA namely KOH. CHA zeolite as a catalyst is easily deactivated due to the formation of cokes on the zeolite microporous framework leading to reduce catalytic ability, hierarchical pore of CHA zeolite is the one of strategy to overcome this problem. Hierarchical pore of CHA zeolite by desilication method using alkaline was reported to be unable to maintain the morphology of the zeolite and lead to reduce the crystallinity and catalytic ability. Formation of hierarchical pore of zeolites with uniform mesoporous and maintaining morphology could be generated by desilication method with the addition of directing mesoporous compounds. In this study, interzeolite transformation of hierarchical pore of FAU zeolite into CHA was carried out using TMAdaOH and using KOH with and without confined-TEABr technique. The hierarchical pore of FAU zeolite as the parent zeolite was obtained by desilication process with the addition of directing mesoporous compounds such as TBABr and CTAB. The results of the XRD characterization from interzeolite transformation hierarchical pore of FAU into CHA using TMAdaOH for 20 and 40 hours shows that the peak intensity of the FAU zeolite decrease with increasing peak intensity of CHA zeolite. Its indicated that the interzeolite transformation using TMAdaOH could via reconstruction mechanism with the same CBU between FAU and CHA zeolite as d6r. In contrast to he results of the diffraction pattern of interzeolite transformation between FAU zeolite to CHA using KOH with and without the confined-TEABr technique were not via a reconstruction mechanism but via an amorphization mechanism. It could be observed from only CHA zeolite peaks was obtained with no FAU zeolite peaks, the amorphous phase was quite dominant, and the obtained of the other zeolites as LTL zeolite with the longer interzeolite transformation process. Interzeolite transformation using KOH with